2020
DOI: 10.18632/aging.102748
|View full text |Cite
|
Sign up to set email alerts
|

Protein disulfide isomerases are promising targets for predicting the survival and tumor progression in glioma patients

Abstract: INTRODUCTION Gliomas are the most common brain and central nervous system (CNS) tumors. According to cancer statistics, gliomas account for approximately 80% of all malignant primary brain tumors and 57.3% of gliomas was glioblastoma (GBM) [1, 2]. Hideo Nakamura et al. reported that the incidence rate for glioma was 6•6 per www.aging-us.com

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 52 publications
(60 reference statements)
0
24
0
Order By: Relevance
“…P4HB, also known as PDIA1, PDI or CLCRP1, is a vital disulfide isomerase, redox enzyme and chaperone in the ER and is regarded as a prognostic factor related to the genesis and progression of multiple carcinomas. [20][21][22] However, the correlation between P4HB and BC remains unclear. Our study demonstrated for the first time that the expression of P4HB was elevated in BC tissues from 80 patients and BC cell lines, which was consistent with results from the TCGA database analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…P4HB, also known as PDIA1, PDI or CLCRP1, is a vital disulfide isomerase, redox enzyme and chaperone in the ER and is regarded as a prognostic factor related to the genesis and progression of multiple carcinomas. [20][21][22] However, the correlation between P4HB and BC remains unclear. Our study demonstrated for the first time that the expression of P4HB was elevated in BC tissues from 80 patients and BC cell lines, which was consistent with results from the TCGA database analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In previously published studies, P4HB and PDIA3 played an important role in diffuse glioma progression and therapeutic outcomes, 23 and the PDI family is associated with the survival and tumor progression of glioma. 22 Moreover, recent research revealed that high P4HB expression is correlated with poor prognosis in hepatocellular carcinoma 15 and could be a potential prognostic biomarker in gastric cancer. 20 P4HB is highly expressed in renal clear cell carcinoma (ccRCC) and positively correlated with pathological grade, stage and poor prognosis; it has been verified as an independent risk factor by multifactor Cox regression in ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…Using “GSVA package”, functional enrichment analysis was performed as previously described [ 30 ] to reveal the mechanisms of action of the aging-related genes in the initiation and progression of gliomas.…”
Section: Methodsmentioning
confidence: 99%
“…Lovat et al ( 26 ) demonstrated that overexpression of wild-type P4HB in melanoma cells decreased the level of apoptosis in response to ER stress, which was beneficial to the survival of tumor cells. Furthermore, recent studies have demonstrated that P4HB is overexpressed in gliomas and that P4HB suppression sensitizes glioblastoma to chemotherapy and radiotherapy by abrogating ER stress-induced UPR signaling ( 10 , 12 , 27 ). These results suggested the clinical importance of P4HB in tumorigenesis and progression.…”
Section: Discussionmentioning
confidence: 99%